Accountability and continuing teacher training: dissonances in offering an integral education - Mielo, Eduardo Guimaraes [UNESP]; Sabia, Claudia Pereira de Padua [UNESP] (Univ Federal Norte Tocantins-ufnt, 2024)
This article discusses the impact of educational accountability policies based on large-scale assessments on the continuing education of teachers and the quality of basic education in Brazil. The study aims to identify how the results of student performance in external assessments (Basic Education Assessment System- Saeb and the Performance Assessment System of the State of S & atilde;o Paulo- Saresp) and their indicators are used to determine the distribution of resources from the Programa de A & ccedil;& otilde;es Articuladas (PAR) and verify the consequences on teacher training from the perspective of Integral Education. Although assessments are seen as tools to achieve quality in education, they end up focusing on meeting goals and indicators, to the detriment of continuous and full teacher and student training. The dissonances between educational policies and pedagogical practice are also highlighted, noting that the pressure to obtain good results in assessments can limit the autonomy of teachers in teacher training programs at state level. It is concluded that accountability policies, by prioritizing quantitative results, disregard the individual needs of students and the human and critical training necessary for a comprehensive and quality education.
Keywords: accountability; teacher training; integral education; large-scale assessment; educational policies